Peran Bahasa Indonesia dalam Pendidikan Guru SD: Tantangan dan Adaptasi di Era Digital - Amanda Liviani Br Muham; Gita Malem Br Karo Sekali; Timanta Agustina Br Purba; M. Surip (Universitas Serambi Mekkah, 2025)
Indonesian has a Central Material in education, especially in the formation of literacy and communication competencies for prospective elementary school teachers. In the digital era, challenges in the use of Indonesian are increasingly complex, along with technological developments, changes in learning patterns, and the rampant use of foreign languages in various digital platforms. This study aims to analyze the role of Indonesian in elementary teacher education and identify the challenges and adaptation strategies needed to remain relevant in the midst of digital dynamics. The research method used is a qualitative approach with literature study analysis and interviews with educators and prospective elementary teacher students. The results showed that although Indonesian remains the main language in learning, there are obstacles such as low interest in digital literacy in Indonesian, the dominance of learning resources in foreign languages, and the lack of technology integration in language teaching. Therefore, adaptation strategies are needed, such as strengthening Indonesian-based digital literacy, developing innovative learning resources, and increasing digital competence for prospective teachers. Thus, Indonesian can continue to play a role as an effective communication and education tool in learning at the elementary school level, while being able to compete in the digital era.